Pengembangan media pembelajaran Gimkit berbasis literasi digital pada mata pelajaran IPAS di SD Negeri 160 Palembang - Silvi Margareta; Kiki Aryaningrum; Mega Kusuma Putri (IKIP Siliwangi, 2026)
This research is a type of development research (Research and Development) which aims to produce interactive learning media in the form of Gimkit based on digital literacy that is valid and practical to be used in Natural and Social Sciences (IPAS) subjects for grade IV at SDN 160 Palembang. The background of this research is based on the problem of low participation and motivation of students in learning IPAS. To answer this problem, an interesting technology-based learning media was developed that is able to increase active student involvement. The development model used is the ADDIE model which includes five stages, namely Analysis, Design, Development, Implementation, and Evaluation. At the validation stage, the media was assessed by three experts, namely media experts, material experts, and language experts. The validation results showed that the media was classified as very valid with scores of 94.6%, 95.3%, and 93.3% respectively. Furthermore, the practicality test was carried out through the one-to-one and small group methods. The one-to-one test obtained a score of 95%, while the small group test obtained a score of 98.8%, both of which are included in the very practical category. The results show that Gimkit media based on digital literacy is effective in increasing student engagement, activeness, and learning motivation. Thus, this media is declared worthy of use as an alternative interactive learning media that supports the science learning process at the elementary school level